2015
DOI: 10.1136/bjsports-2014-093877
|View full text |Cite
|
Sign up to set email alerts
|

Repeated head trauma is associated with smaller thalamic volumes and slower processing speed: the Professional Fighters’ Brain Health Study

Abstract: ObjectivesCumulative head trauma may alter brain structure and function. We explored the relationship between exposure variables, cognition and MRI brain structural measures in a cohort of professional combatants.Methods224 fighters (131 mixed martial arts fighters and 93 boxers) participating in the Professional Fighters Brain Health Study, a longitudinal cohort study of licensed professional combatants, were recruited, as were 22 controls. Each participant underwent computerised cognitive testing and volumet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
116
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(131 citation statements)
references
References 25 publications
10
116
2
3
Order By: Relevance
“…In addition, paths involving cingulum, hippocampus, parahippocampus, amygdala, and thalamus showed a significantly lower WM connectivity in cognitively impaired fighters, and all these regions have been implicated to be involved in memory (Johns, ). Furthermore, in this same cohort, volumetric loss in thalamus and its association with neuropsychological outcomes (Bernick et al, ) has been indicated to predict cognitive decline (Mishra et al, ) due to RHI. These findings suggest that the RHI in fighters exhibiting cognitive decline had a significant WM connectivity damage in regions involving executive and working memory which may be responsible for their poor functional outcome.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, paths involving cingulum, hippocampus, parahippocampus, amygdala, and thalamus showed a significantly lower WM connectivity in cognitively impaired fighters, and all these regions have been implicated to be involved in memory (Johns, ). Furthermore, in this same cohort, volumetric loss in thalamus and its association with neuropsychological outcomes (Bernick et al, ) has been indicated to predict cognitive decline (Mishra et al, ) due to RHI. These findings suggest that the RHI in fighters exhibiting cognitive decline had a significant WM connectivity damage in regions involving executive and working memory which may be responsible for their poor functional outcome.…”
Section: Discussionmentioning
confidence: 83%
“…Magnetic resonance imaging (MRI) can be used to investigate changes in regional brain volumes, perfusion, structural connectivity [derived using diffusion‐weighted MRI (dMRI)], and functional connectivity in participants exposed to RHI. For instance, various structural neuroimaging studies of RHI due to combat sports and in veterans with blast injuries have shown changes in various gray matter volumes such as thalamus, ventromedial prefrontal cortices, right fusiform gyrus, and frontotemporolimbic regions involving hippocampus, medial temporal lobe, and frontal lobes (Bernick et al, ; Bigler, ; Gooijers et al, ; Lopez‐Larson et al, ; Mishra et al, , ; Montenigro, Bernick, & Cantu, ; Ng et al, ). Similarly, voxelwise dMRI‐derived measures such as fractional anisotropy (FA) and mean diffusivity (MD) have shown differences in the temporo‐occipital white matter tracts and forceps major (Hulkower, Poliak, Rosenbaum, Zimmerman, & Lipton, ; Mishra et al, ; Ng et al, ; Orrison et al, ; Shin et al, ; Wintermark, Sanelli, Anzai, Tsiouris, & Whitlow, ; Zhang et al, ; Zhang, Heier, Zimmerman, Jordan, & Ulug, ).…”
Section: Introductionmentioning
confidence: 99%
“…This program results in volumes and cortical thickness of pre-set regions of the entire brain. We were particularly interested in the thalamus and caudate, because these regions had been shown in our earlier research to be related to exposure and cognition, 6 and in the hippocampus, given its role in Alzheimer's disease and in older adults with an APoE e4 allele.…”
Section: Discussionmentioning
confidence: 99%
“…Further, correlations existed between these regions and cognitive ability, suggesting a functional impact of the anatomic-fight exposure relationship. 6,7 More recently, we started to collect genetic data on participants. We tested the hypothesis that previously revealed that relationships would be moderated by e4 status.…”
Section: Introductionmentioning
confidence: 99%
“…A greater number of prior boxing bouts was correlated with worse cognitive performance among amateur male boxers in the late 1980s,4 and a more extensive history of professional boxing or mixed martial arts fighting may be related to a lower volume of subcortical brain structures responsible for processing speed 5. Furthermore, visual function deficits have been observed immediately after a three-round sparring session compared with prebout performance among a mixed cohort of amateur boxers and mixed martial arts athletes 6.…”
Section: Introductionmentioning
confidence: 97%